The Mexican corrido and the cordel literature: Traditional poetic tessitures in transit through telecollaborative network - Marques, Francisco Cláudio Alves [UNESP]; da Silva Conessa, Gabriel [UNESP]; de Lima, Gustavo Henrique Alves [UNESP] (Springer Nature, 2023)
This article aims to make some considerations about two poetic traditions from the Iberian romancer: the Mexican corrido and the cordel literature. The discussion on the subject was triggered by a virtual meeting with students from the University of Mexico, within the framework of the project Capes/PrInt/UNESP: Diffusion of culture, language and literature in contexts of telecollaboration, an occasion that was conducive to the debate around cultures from the Iberian Peninsula that acclimated to the dictions and sociocultural context of the New World. It is basically a question of sketching some lines about the historical and sociocultural confluences that helped foster a literature that, despite having preserved some of the main characteristics common to the Iberian aspect, gained new purposes and characteristics of its own to express the peculiarities of the reception context.
Keywords: Cordel literature; Iberian tradition; Mexican corrido; Telecollaborative networks